SUDDEN DEATH OFA MIDDLEAGED DRIVER BY THROMBOEMBOLISM (Journal of Forensic Medicine & Toxicology, 2018)
A detached thrombus or part of thrombus is carried by steam of blood flow in blood vessels constitutes most common for fatal and sudden natural deaths. Debility in old age, immobility, trauma, bed rest are the main cause  for stasis in veins especially in lower legs. Alteration in one or more components of Virchow’s triad include hypercoagubality, stasis and damage to vascular endothelium attributes pathophysiology of venous
Keywords: Deep vein thrombosis; pulmonary embolism; venous thrombo embolism